Keberadaan Kegiatan Baca Al-Qur’an Dala Pembelajaran Di Kelas Sebagai Implementasi Hidden Curriculum - Tety Rukmanah; Hindun Hindun (Lembaga Pengembangan Kinerja Dosen, 2024)
Hidden curriculum in schools has an important role in building students' perceptions, personalities and attitudes. So far, teachers have only focused on the curriculum guidelines that have been set by policy makers (formal curriculum), and have not utilized other factors outside those that have been set (hidden curriculum). Therefore, this research was conducted with the aim of analyzing the existence of Al-Qur'an reading activities in classroom learning as an implementation of the hidden curriculum. The form of research used in this research is qualitative research. This research is descriptive in nature by collecting data from explanations of research subjects, observations and other sources. The results of the research can be concluded that the activities carried out in the form of a hidden curriculum have proven to be very effective in instilling religious values in students by applying habituation methods, one of which is the habit of tadarus al-Qur'an, memorizing verses of the Koran, do' every day, chant Asmaul Husna and always behave well and responsibly and carry out the commands of Allah SWT and stay away from all His prohibitions. Implementing this activity is an activity that is very beneficial for students in everyday life and life in the future. In order for a program to run as expected, there needs to be more supervision, motivation and evaluation every weekend so that activities can run well and always produce a positive impact on students.